IMPLEMENTASI SISTEM ONLINE SINGLE SUBMISSION RISK BASED APPROACH (OSS RBA) DALAM PELAYANAN PERIZINAN BERUSAHA DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN SEMARANG - Putri Namiroh, Dinda; Lituhayu, Dyah; Larasati Setianingsih, Endang (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Simplification of the licensing system has been implemented by the government through the application of the electronic-based licensing system, Online Single Submission Risk-Based Approach (OSS RBA), which classifies business levels based on risk. According to data from the Department of Cooperatives and SMEs of Semarang Regency in 2023, out of a total of 85,990 MSMEs in the region, only 14,307 (16.6%) have obtained business licenses. Moreover, the absence of a digital Detailed Spatial Plan (RDTR) and supporting OSS systems has made the KKPR process and licensing verification complicated and complex. This study aims to understand the implementation of the OSS RBA system in business licensing services at the DPMPTSP of Semarang Regency and the factors that influence it. The method used in this research is qualitative descriptive, with data collection techniques including interviews, observations, and literature studies. The study employs Van Meter & Van Horn's policy implementation theory. The results show that management and infrastructure have achieved optimal outcomes. However, human resources are still inadequate because staff members lack proficiency in the system, hindering their ability to provide assistance. Furthermore, work relationship structures and the development of support systems have not yet yielded optimal results. The inhibiting factors include the complexity of the OSS migration process and inter- organizational communication issues, as many technical departments do not fully understand the OSS system, lack clear SOPs, and have human resources that do not meet the required competencies. Meanwhile, the supporting factors include the characteristics of the implementing organization, the attitudes of the implementers, and the socio-economic and political environment. The recommendations provided in this study include the enhancement of human resource capacity with a focus on the use of information technology, the acceleration of digital RDTR preparation, and the rapid development of support systems to integrate manual licensing and track licensing verification.